Morphological study of styloid process and its variations in human skull - MUKESH KUMAR,; SANKARAN P K,; YUVARAJ M,; GUNAPRIYA R,; ZAREENA BEGUM, (International Journal of Pharma and Bio Sciences, 2017)
Styloid process is a thin elongated piece of bone projecting downwards from the inferior surface of temporal bone and gives attachment to three muscles and two ligaments. The aim of this study was to know the morphometry of various parameters in styloid process and its clinical significance. In this study, 96 skulls were used out of which 11 skulls had length more than 3cm indicating elongated styloid process. The elongated styloid process had significant variations in anterior angle, distance from its tips and its bases. These variations can compress the important vessels and nerves around it. These may be useful for surgeons, radiologists, otorhinolaryngologists , and dentists for diagnosing these types of signs and syndromes.